Pengaruh Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai Pada BPJS Ketenagakerjaan Kota Jambi - Khalilah Fitrhiyah (Science of Management and Students Research Journal (SMS), 2022)
Work supervision plays a very important role in employee performance. Therefore, the purpose of  this research is to describe the work supervision and performance of employees at work, and to find out and analyze the effect of work supervision employee performance at work in SDN 179 Tanjung Jabung Timur Kecamatan Nipah Panjang. Research methods in this study is descriptive and quantitative method. Data analyze use SPSS Ver 22 and using models simple linier regression with result of count Y = 1,116+0,527X+e. The test of determination with R2 of 37,6%. T test by comparison tcount 3,547 > ttable 0,3338 then Ho accepted Hi be. Rejected. To analyze the effect of work supervision on performance of employees on SDN 179 Tanjung Jabung Timur Kecamatan Nipah Panjang. The distribution of questionnaires with a population of 35 people in 2021 , then the formula used to find samples according to Istijanto (2009 :114)so that the sample in this study amounted to 35 people respondent.Work supervision regression coefficient (X) is 0,525, meaning that work supervision (X) has increased by 1%, so performance of employees at work (Y) SDN 179 Tanjung Jabung Timur Kecamatan Nipah Panjang. The coefficient of determination is known from the value of R2=0,376 (37,6%) which means that work supervision(X) is able to explain performance of employees at work (Y) at the SDN 179 Tanjung Jabung Timur Kecamatan Nipah Panjang that is equal to 37,6% and the remaining 62,4% is influenced by other variables. Not investigated in this study. Based on t-test, t-count value is 3,547  and the t-table is 0,3338. From the comparison results, it can be seen that  the test by comparison tcount 3,547 > ttable 0,3338 then Ho accepted Hi be. Rejected. Meaning that Work supervision affect c performance of employees at work at SDN 179 Tanjung Jabung Timur Kecamatan Nipah Panjang.